Nutritional Strategies to Combat Chronic Inflammation and Promote Wellness - chandrakar, Nidhi; Singh, Jai Prakash; Antiwal, Meera; Maurya, Pranshu kumar (International Research Journal of Ayurveda & Yoga, 2025)
Background: This study explores the impact of diet on inflammation and its role in preventing chronic diseases such as cancer, cardiovascular disorders, and autoimmune conditions. It aims to identify dietary factors that contribute to or reduce inflammation and highlight essential nutrients that support immune function. Methods: A review of existing literature and scientific studies was conducted to analyze the relationship between dietary components and inflammatory responses. Specific attention was given to the effects of pro-inflammatory foods (e.g., processed meats, sugary beverages, alcohol) and anti-inflammatory foods (e.g., fruits, vegetables, nuts, healthy fats). The role of vitamins and minerals, including zinc, selenium, and antioxidants such as vitamins C and E, was examined in modulating inflammation. Observations: The findings indicate that excessive consumption of processed and high-sugar foods exacerbates inflammation, while a nutrient-dense diet rich in antioxidants, fiber, and healthy fats can mitigate inflammatory responses. Key anti-inflammatory foods, such as olive oil, flaxseed, turmeric, and garlic, were identified for their beneficial properties. Essential micronutrients, including vitamin B complex, vitamin D, and carotenoids, were found to play a crucial role in immune function and inflammation control. Discussion: A well-balanced diet that prioritizes anti-inflammatory foods can significantly reduce chronic inflammation, enhance immune defense, and lower the risk of metabolic and inflammatory diseases. Nutritional interventions, including increased intake of vitamins, minerals, and antioxidants, are effective in managing inflammation and promoting long-term health. Conclusion: The study concludes that dietary modifications are a crucial strategy for disease prevention and overall well-being.